Pengembangan Kreatifitas Keberbakatan Di Paud Griya Bermain Pangkalpinang Bangka - Makmun, Puri Handayani (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2017)
This research aimed to describe the Creativity development of giftedness in Griya Bermain early childhood education programs Pangkalpinang Bangka. Approach is a qualitative to the type of research description. Data were obtained through intervew, observation, dan documentation and were analyzed using the model. Then tested its validity through persistensice observation and triangulation. The result showed that the the Creativity development of giftedness in Griya Bermain early childhood education programs Pangkalpinang Bangka. Include, (1) Identify creativity of gifted children at school Information obtained from parents, learning process, Information from the child itself, Information from his friend, Not yet the identification "screening" Stage. (2) Creativity development of child giftedness in Griaya Bermain early childhood education programs Already facilities and infrastructure although not maximal and educators who already have undergraduate qualifications (S1). (3) Obstacles in developing the creativity of childrens talent in Griya Bermain early childhood education programs that is, there are still parents who only prioritize cognitive aspects Such as focus on read, write and count and unbalanced attention to aspects of psychomotor and affection.